Prevalence of pre-clinical and clinical obesity in adults: Pooled analysis of 56 population-based national health surveys. - Rodrigo M Carrillo-Larco; Wilmer Cristobal Guzman-Vilca; Carla Tarazona-Meza; Xiaolin Xu; Antonio Bernabe-Ortiz (PLOS Global Public Health)
Obesity is commonly defined using body mass index (BMI), but BMI alone does not capture the metabolic and functional consequences of excess weight. We examined the prevalence of clinical obesity, a new definition that incorporates BMI alongside metabolic and functional impairments. We analyzed nationally representative surveys. Clinical obesity was defined as BMI ≥ 30 kg/m2 and waist-to-height ratio ≥0.5 or BMI ≥ 40 kg/m2 with at least: self-reported diabetes, fasting plasma glucose ≥126 mg/dl, self-reported hypertension, blood pressure ≥140/90 mmHg, or total cholesterol ≥200 mg/dl. We estimated the survey-weighted and age-standardized prevalence of clinical obesity and BMI-only obesity by country and sex. Data from 56 countries were included (n = 142,250). The prevalence of clinical obesity ranged between 0% and 29%. The prevalence of clinical obesity was < 10% in 41 countries for men and 30 for women. In men, the largest shift in prevalence of BMI-only obesity and clinical obesity was observed in Malawi (0.7% vs 0.2%, relative change: -68%); in women, the largest shifts in prevalence were seen in Malawi (5.6% vs. 2.6%, relative change: -53%) and Rwanda (2.7% vs. 1.3%, relative change: -52%). The adoption of clinical obesity criteria revises obesity prevalence estimates and highlights metabolic and functional impairments beyond BMI. Our results emphasize the need to carefully consider how obesity is defined in population surveillance to ensure its relevance to health outcomes.